Fabrication of Mn/P co-doped hollow tubular carbon nitride by a one-step hydrothermal–calcination method for the photocatalytic degradation of organic pollutants. Issue 18 (17th August 2022) - Wang, Dongbo; Dong, Xiyuan; Lei, Ye; Lin, Changqing; Huang, Dan; Yu, Xin; Zhang, Xuan
Abstract : Efficient photocatalytic degradation of trace organic pollutants in aqueous environment by a hollow tubular carbon nitride co-doped with manganese and phosphorus under visible light. Abstract : Photocatalytic degradation of pollutants is regarded as an economical and environmentally-friendly strategy. Herein, a hollow tubular carbon nitride photocatalyst co-doped with manganese and phosphorus (Mn–PCN) was synthesized by a one-step hydrothermal–calcination method and used for the photocatalytic degradation of organic pollutants. Introducing P shaped the tubular morphology, increased the specific surface area, and enhanced the light efficiency. Adding Mn narrowed the band gap, regulated the tubular morphology, and affected the electronic structure. Co-doping P and Mn enhanced the photocatalytic performance synergistically. Compared with pure carbon nitride (CN), the photocatalytic performance of Mn–PCN was greatly improved. Rhodamine B could be removed almost completely in 150 min with 3Mn–PCN, and the degradation rate constant k was 0.01924, which was 14 times that of CN. Meanwhile, 3Mn–PCN could remove 99% of tetracycline hydrochloride, 57% of bisphenol A, and 68% of sulfamethoxazole. The Mn–PCN structure was identified and the possible mechanism was proposed according to DFT calculation and experimental results. The results provide new insights into rational design of highly active catalysts with visible light sensitive activity.